Inter‐Arm Blood Pressure Differences in Young, Healthy Patients. Issue 8 (10th May 2013) - Grossman, Alon; Prokupetz, Alex; Gordon, Barak; Morag‐Koren, Nira; Grossman, Ehud
Abstract : The prevalence and magnitude of inter‐arm BP difference (IAD) in young healthy patients is not well characterized. Flight academy applicants and designated aviators undergo annual evaluation that includes blood pressure (BP) measurement on both arms. All BP measurements performed from January 1, 2012, to April 30, 2012, were recorded and IAD was calculated. Results were compared between patients in whom BP was initially measured in the right arm (group 1), those in whom BP was initially measured in the left arm (group 2), and those in whom the arm in which BP was initially measured was not recorded (group 3). A total of 877 healthy patients had BP measured during the study period. In the entire group, mean systolic BP was the same in both arms. Absolute IAD was 5.6±5.5 mm Hg for systolic and 4.7±4.5 mm Hg for diastolic BP. IAD >10 mm Hg was recorded in 111 (12.6%) and 77 (8.8%) patients for systolic and diastolic BP, respectively. IAD was the same in the 3 groups and was unrelated to age, body mass index, and heart rate, but was related to systolic BP. IAD is common in young healthy patients, is not dependent on which arm was measured first, and unrelated to age, body mass index, and heart rate.